2002
DOI: 10.1177/152660280200900112
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Stenting for Chronic Iliac Artery Occlusion

Abstract: Stenting of chronic iliac occlusions is a safe and durable alternative to surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 39 publications
1
36
2
1
Order By: Relevance
“…Compared with these data, we observed an improved mid-term outcome in our study with lower embolic complication rates than reported in other studies [3,14]. One of the reasons for this is that we employed the laser as a debulking device prior to stent implantation, which might reduce the incidence of distal embolization as well as restenosis by creating a smoother plaque surface below the stent.…”
Section: Discussioncontrasting
confidence: 66%
“…Compared with these data, we observed an improved mid-term outcome in our study with lower embolic complication rates than reported in other studies [3,14]. One of the reasons for this is that we employed the laser as a debulking device prior to stent implantation, which might reduce the incidence of distal embolization as well as restenosis by creating a smoother plaque surface below the stent.…”
Section: Discussioncontrasting
confidence: 66%
“…Recent series of primary stent placement for CTOs reported the 2-year primary and secondary or assisted primary patency rates of 69%-93% and 85%-95%, respectively. [3][4][5][6][7][8][9][10][11][12] Our series demonstrated 2-year primary and assisted primary patency rates of 91% and 96%, at the high end of the range of recent reports. However, although our patency rates for primary stents placed for iliac CTOs were better than those reported for extra-anatomic bypasses, such as axillofemoral and femorofemoral bypasses, these patency rates were not better than the patency conventionally reported for aortobifemoral bypass.…”
Section: Discussionmentioning
confidence: 49%
“…The 5-year primary and assisted primary patency rates were 55%-85% and 66%-95%, while those at 10 years was 68% (Table 2). 4,[7][8][9][10]12 Primary patency rates of aortobifemoral bypass for patients with claudication were reported to be 91.0% and 86.8% at 5 and 10 years, respectively, while 87.5% and 81.8% for patients with critical limb ischemia. 25 To date, the long-term durability appears to be better in aortobifemoral bypass than in primary stent placement, but it is highly likely that during the next few years endovascular techniques will be further refi ned, thereby leading an improved longterm durability.…”
Section: Discussionmentioning
confidence: 96%
“…In Tabelle 3 sind die Offenheitsraten aus Metaanalysen der interventionellen und gefäßchirurgischen Therapie aufgeführt, wobei es sich nicht um randomisierte oder kontrollierte Studien handelt [62][63][64][65][66][67][68][69][70][71][72]. Trotzdem bietet diese Zusammenstellung aktueller Studienergebnisse eine Grundlage für die individuelle Therapieempfehlung bei der Indikation zur Revaskularisation [73].…”
Section: Endovaskuläre Therapie Der Pavkunclassified